Probiotic Properties of Lactobacillus helveticus and Lactobacillus plantarum Isolated from Traditional Pakistani Yoghurt - Hassan, Mahreen Ul (Biomed Res Int, 2020)
Probiotic bacteria are of utmost importance owing to their extensive utilisation in dairy products and in the prevention of various intestinal diseases. The objective of this study was to assess the probiotic properties of bacteriocin-producing isolates of Lactobacillus helveticus and Lactobacillus plantarum isolated from traditional Pakistani yoghurt. In this study, ten bacteriocin-producing isolates were selected to screen for the probiotic property. The isolates showed resistance to acidic pH (6-6.5), bile salt (0.01-1%), and 1-7% NaCl salt and showed good growth at acidic pH and antibacterial activity against ten different foodborne pathogens. Interestingly, these isolates were proved to be effective against Actinobacter baumannii but least effective against Klebsiella pneumoniae and Pseudomonas aeruginosa. A few isolates were found to be resistant to some antibiotics like vancomycim, gentamycin, erythromycin, streptomycin, and clindamycin. Our results provide strong evidence in favour of traditional Pakistani yoghurts as a potential source of bacteriocin-producing bacteria with an added benefit of the probiotic property. Specifically, LBh5 was considered a good probiotic isolate as compared to other isolates used in the study. Further extensive research should be done on isolation and characterisation of probiotic isolates from local fermented foods, and then, these isolates should be used in the development of probiotic enriched food supplements in Pakistan.